2022
DOI: 10.1017/s1355617722000686
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of neurocognitive and psychological functioning in adults with early-treated phenylketonuria

Abstract: Objective: Relative to youth with early-treated phenylketonuria (ETPKU), much less is known regarding the cognitive profile of adults with ETPKU. The present study aimed to address this gap by providing a comprehensive assessment of neuropsychological functioning among adults with ETPKU. Method: A sample of 40 adults with ETPKU (ages 18 – 36) and a demographically matched group of 32 healthy individuals without PKU participated. Participants completed a comprehensive neuropsychological b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The groups did not differ significantly in anxiety; however, high anxiety was more common in the ETPKU group (53% of sample) than the non-PKU group (33%). Previous findings on the association between anxiety symptomatology and Phe levels have been equivocal, with some observing a relationship (e.g., Clacy et al, 2014; Clocksin et al, 2023; Waisbren et al, 2017) and others not (e.g., Brumm et al, 2004; Burton et al, 2013; Jahja et al, 2017; Weglage et al, 2000). Within this context, we found no relationship between current or historic Phe levels and anxiety symptomatology.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The groups did not differ significantly in anxiety; however, high anxiety was more common in the ETPKU group (53% of sample) than the non-PKU group (33%). Previous findings on the association between anxiety symptomatology and Phe levels have been equivocal, with some observing a relationship (e.g., Clacy et al, 2014; Clocksin et al, 2023; Waisbren et al, 2017) and others not (e.g., Brumm et al, 2004; Burton et al, 2013; Jahja et al, 2017; Weglage et al, 2000). Within this context, we found no relationship between current or historic Phe levels and anxiety symptomatology.…”
Section: Discussionmentioning
confidence: 93%
“…They reported the largest effect for WM-related symptoms/behaviors, with 19% of children and 29% of adults scoring in the "abnormally elevated" range on the associated scale. In another recent comprehensive study of neurocognitive functioning in adults with ETPKU, Clocksin et al (2023) found that ETPKU-related impairments in EF were most apparent on a computerized WM list sorting task (as compared to the other EF tasks that were administered). Within their ETPKU group, EF performance was also strongly correlated with recent metabolic control (as reflected by blood Phe levels).…”
mentioning
confidence: 98%
“…Although childhood Phe remains the most important determinant of early and late neurocognitive outcomes, the limited effectiveness of MNT in the long term can still increase the risk for developing deficits in neurocognitive functioning in adulthood [ 15 , 37 , 39 , 41 , 42 , 46 , 47 , 148 , 149 ]. Even when controlling for historic Phe levels, adults were reported to experience cognitive difficulties in executive functioning, processing speed, motor skills and visuospatial skills, of which the severity correlated with concurrent blood Phe concentrations [ 37 , 148 , 150 ]. There is therefore no debate on the need for lifelong treatment to prevent these PKU-related cognitive symptoms.…”
Section: Discussionmentioning
confidence: 99%